Evaluation of a web-based self-help intervention for patients with generalized anxiety disorder: protocol for a randomized controlled trial - Rubel, Julian; Quest, Jannis; Prüßner, Luise; Timm, Christina; Hartmann, Steffen; Barnow, Sven; Rittmeyer, Lisa; Rosenbaum, David; Lalk, Christopher (JMIR Research Protocols, 2023)
Background: Generalized anxiety disorder (GAD) is a highly prevalent and severely distressing condition that can lead to functional impairments and is considered one of the most difficult anxiety disorders to treat. Following new technological developments, a highly structured cognitive behavioral therapy (CBT) approach that has already shown success in face-to-face psychotherapy can be implemented: internet-delivered CBT (iCBT). There is now evidence for the efficacy of both guided and unguided iCBT interventions for GAD regarding symptom reduction. Objective: To establish the usefulness of such interventions, we plan to evaluate the efficacy of a web-based self-help program (Selfapy) for GAD in a relatively large sample. We aim to assess effects beyond symptom reduction, including effects on well-being, functioning, and mental health literacy, as well as the effect on health care burden, while testing the intervention in conditions comparable to routine care. Methods: Patients (n=156) who have been diagnosed with GAD, are aged between 18 and 65 years, have internet access, and have sufficient German language skills will be recruited for this study. The intervention group (n=78) will receive access to the 12-week self-help web-based program Selfapy. The waitlist control group (n=78) will receive no intervention in the context of the study. However, both groups will be allowed to access further health care services (eg, psychotherapy, medication), reflecting current routine care in Germany. Outcome measures will be assessed at baseline (T1) and 6 weeks (T2) and 12 weeks (T3) after the start of the intervention. The primary outcome will be generalized anxiety symptoms and quality of life at T3. Additional outcomes include depression, work capacity, therapy-related expenses and burdens, health literacy, and negative effects. Results: By May 2023, all participants had finished the trial and the report was being prepared for publication. Conclusions: Web-based interventions may be an important addition to the German health care system to reduce barriers to treatment access. Further, they may prove cost-effective for the treatment of GAD. Clinical Trial: Deutsches Register Klinischer Studien DRKS00023799; https://tinyurl.com/22bds38x